Modeling and Control of a DFIG-Based Wind Turbine During a Grid Voltage Drop - Babaie Lajimi, A.; Asghar Gholamian, S.; Shahabi, M. (Engineering, Technology & Applied Science Research, 2011)
Doubly-fed induction generators (DFIG) are widely used in wind energy generation systems. During a grid voltage drop, performance is degraded with rotor over current deteriorating the fault-ride through (FRT) capability of the DFIG wind-energy generation system. In this paper, a complete mathematical DFIG model is proposed. The rotor is considered fed by a voltage source converter whereas the stator is connected to the grid directly. Output power and electromagnetic torque are controlled using field-oriented control (FOC). Simulation results show the efficiency of the controller in exploiting the maximum power of wind.